Reconfiguração do mercado brasileiro de música : os incumbentes e os novos capitais - Toyama, Míriam Costa (Universidade Federal de São Carlos, 2015)
This doctoral dissertation seeks to explain the changes in the music market in the last decade using the Field Theory, by Fligstein and McAdam (2012). Thus, we consider the music market a strategic field of action, which, according to the authors is in frequent adjustment and are subject to external shocks. In this way, through events in nearby fields, the development of innovations that allowed the unauthorized sharing and downloading content over the internet has had a profound impact on the music market, and later on other cultural goods markets. Initial reactions of the incumbent actors have been through strategies that had already been used in earlier times: law suits, educational campaigns and pressuring the government in favor of a stronger legislation. Thus, the reactions of incumbent actors were acoording to what explains the theory, the use of strategies known to restore the status quo. However, due to the crisis that shook the ability of incumbent actors to reproduce their advantages, new players entered the market. In addition, incumbent actors gave way and changed their business models, establishing relations with the new entrants, and adopting new business models leveraging the internet as a means of distribution, dissemination and others. Record companies also started expande their activtities, working with artist's career management. Thus, according to the analysis of the work, we concluded that there was a change in the business model, and that in the Brazilian case these changes followed the international trends. Through research field we conclude that Brazilian companies have adopted the distribution of digital music through online stores and through cell phone companies, streaming services as well as the actors have adopted the 360 contracts.
Keywords: Indústria fonográfica; Mercado brasileiro de música; Teoria dos campos; Modelos de negócios; Brasilian music market; Brasilian music industry; Theory of fields; Business models; ENGENHARIAS